Development of Augmented Reality Based Wushu Training Module to Improve Basic Movement Ability - Ramdhan, Syaipul; Asoka, Egga (JURNAL SISFOTEK GLOBAL, 2021)
Wushu martial arts is one of the favorite martial arts in Indonesia, with achievements that are routinely obtained at various international events such as the SEA Games and ASIAN Games including the World Championships. During this pandemic, wushu college students practice independently, in fact only a few universities have started practicing together by implementing health protocols. Therefore, the researchers developed a wushu training module using Augmented Reality technology, which will be a fun new tool for Sasana Wushu Salsabila Indonesia students. Interactivity and three-dimensional display are presented in an attractive manner and can be used anywhere and anytime. This training module is an android application. Students can find out in detail the correct movement according to existing standards, namely IWUF (International Wushu Federation). This research method uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation).